2004 IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.2004.1325955
|View full text |Cite
|
Sign up to set email alerts
|

Spectral entropy based feature for robust ASR

Abstract: Abstract. In general, entropy gives us a measure of the number of bits required to represent some information. When applied to probability mass function (PMF), entropy can also be used to measure the "peakiness" of a distribution. In this paper, we propose using the entropy of short time Fourier transform spectrum, normalised as PMF, as an additional feature for automatic speech recognition (ASR). It is indeed expected that a peaky spectrum, representation of clear formant structure in the case of voiced sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
4

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 6 publications
1
69
0
4
Order By: Relevance
“…Instead of transforming the spectral information into cepstral domain, we suggested computing entropy from the sub-bands of spectrum and trying to locate the spectral peaks of the spectrum which are supposed to be more robust to noise. In [4], we showed that the proposed multiresolution spectral entropy feature is not very competitive when compared to the state-of-the-art PLP cepstral features, but improves the robustness of the ASR system when appended to the PLP features.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Instead of transforming the spectral information into cepstral domain, we suggested computing entropy from the sub-bands of spectrum and trying to locate the spectral peaks of the spectrum which are supposed to be more robust to noise. In [4], we showed that the proposed multiresolution spectral entropy feature is not very competitive when compared to the state-of-the-art PLP cepstral features, but improves the robustness of the ASR system when appended to the PLP features.…”
Section: Introductionmentioning
confidence: 97%
“…The importance of formants is well know and in [7] the author has tried to use the location of spectral peaks as an additional feature in ASR. On the similar lines, the central idea in [4] while using multi-resolution spectral entropy as a feature was to capture the peaks of the spectrum and their location. To compute entropy of a spectrum we converted the spectrum into a PMF like function by normalizing it.…”
Section: Motivationmentioning
confidence: 99%
See 3 more Smart Citations